2003
DOI: 10.1002/humu.10238
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of theBRCA1-interacting genesZNF350/ZBRK1andBRIP1/BACH1amongBRCA1andBRCA2-negative probands from breast-ovarian cancer families and among early-onset breast cancer cases and reference individuals

Abstract: Two potential breast cancer susceptibility genes, encoding the BRCA1-interacting proteins ZNF350 (or ZBRK1) and BRIP1 (or BACH1), have been identified in yeast two-hybrid screens. We sequenced these genes in probands from 21 families with potentially inherited breast/ovarian cancer, all of which were negative for BRCA1/BRCA2 mutations. Families had at least one case of male breast cancer, two cases of ovarian cancer, or three or more cases of breast and ovarian cancer. In addition, 58 early-onset (before age 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 14 publications
(18 reference statements)
9
47
0
Order By: Relevance
“…Several subsequent studies screened the BRIP1 coding sequence in large numbers of BRCA1/2 negative familial breast cancer families from populations in Northern Europe (Luo et al, 2002;Karppinen et al, 2003;Vahteristo et al, 2006), North America (Rutter et al, 2003) and Australia (Lewis et al, 2005). This resulted in the detection of one frameshift mutation and several missense mutations, none of which segregated with breast cancer in the families.…”
Section: Breast Cancermentioning
confidence: 99%
“…Several subsequent studies screened the BRIP1 coding sequence in large numbers of BRCA1/2 negative familial breast cancer families from populations in Northern Europe (Luo et al, 2002;Karppinen et al, 2003;Vahteristo et al, 2006), North America (Rutter et al, 2003) and Australia (Lewis et al, 2005). This resulted in the detection of one frameshift mutation and several missense mutations, none of which segregated with breast cancer in the families.…”
Section: Breast Cancermentioning
confidence: 99%
“…These data suggest that BRIP1 is a good candidate for moderate/low penetrance genetic susceptibility to breast BRIP1 polymorphisms in breast cancer susceptibility cancer. Previous studies have analyzed potential associations between BRIP1 variants and breast cancer risk, either by mutation analysis or by genotyping, to select single nucleotide polymorphisms (SNPs) within the gene (Lei and Vorechovsky, 2003;Rutter et al, 2003;Sigurdson et al, 2004;Lewis et al, 2005;Garcia-Closas et al, 2006;Vahteristo et al, 2006). Although the rs2048718 (5ꞌ-untranslated region, UTR), rs4988345 (exon 15), and rs4986764 (exon 18) polymorphisms have been previously examined in the context of breast cancer, these genetic association studies have failed to produce consistent results (Luo et al, 2002;Lei and Vorechovsky, 2003;Song et al, 2007;Pabalan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…FANCJ binds and acts with TopBP1 in early DNA replication checkpoint control (34), which suggests that FANCJ has additional roles in the response to replication stress (35) and operates in a parallel pathway to the classic FA pathway (36). Several genotyping studies have identified the association between FANCJ mutations and FA clinical abnormalities (19,20), breast cancer risk (18,(37)(38)(39)(40)(41)(42), and ovarian cancer risk (22). Two FANCJ missense mutations, arginine to cysteine at residue 251 (R251C) and glutamine to histidine at 255 (Q255H), have been reported in FA patients (Fanconi Anemia Mutation Database) (19).…”
mentioning
confidence: 99%